Damage of the reinforced composite material taking into account the laying scheme - Bobyr, Mukola; Pham, Quan Duc; Timoshenko, Oleksandr (Mechanics and Advanced Technologies, 2021)
Expanding the use of reinforced composite materials (RCM) in the power elements of structures for various purposes requires reasonable provision of its load-bearing capacity at the design stage and residual life at the stage of operation. Suitable high-load elements made of RCM have anisotropic mechanical properties and brittle fracture. Analysis of the literature shows that today there are virtually no phenomenological models of deformation and criteria for the destruction of anisotropic RCM, taking into account the damage. Knowledge of these parameters allows you to significantly clarify the stress-strain and limit states of the responsible elements for different purposes. In this study, models are proposed to determine the limit value of the damage of the RCM, which takes into account the scheme of laying each layer under different conditions of simple loading (tension, compression, shear). The limits of use of the models presented in the work are limited by the maximum number of layers in the RCM (up to seven layers). Curves of damage accumulation kinetics are presented using the energy method proposed by Dziuba, which is based on the change of entropy of materials during deformation for RCM with different combination of layer layouts. The parameters of the models were determined, which in turn showed the inexpediency of taking into account all the parameters - neglect of which does not significantly affect the ability of models to predict the limit values of damage.